2018
DOI: 10.1161/jaha.118.009857
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Predictors, and Outcomes of Implantable Cardioverter‐Defibrillator Discharge Among People Living With HIV

Abstract: BackgroundPeople living with HIV (PHIV) are at an increased risk for sudden cardiac death, and implantable cardioverter‐defibrillators (ICDs) prevent SCD. There are no data on the incidence, predictors, and effects of ICD therapies among PHIV.Methods and ResultsWe compared ICD discharge rates between 59 PHIV and 267 uninfected controls. For PHIV, we tested the association of traditional cardiovascular risk factors and HIV‐specific parameters with an ICD discharge and then tested whether an ICD discharge among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In the same cohort, we have previously shown that PLHIV who are prescribed protease inhibitors are associated with significantly increased CV mortality compared to the PLHIV who were prescribed a non-protease inhibitor ART regimen 8 . In another study, our group has also demonstrated that PLHIV with an ICD have a higher rate of ICD firing and subsequently an increased risk of CV mortality compared to the non-HIV individuals 14 . Therefore, from the previous results, it may be plausible that the poor HF outcomes among PLHIV are multifactorial, contributed by different elements.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In the same cohort, we have previously shown that PLHIV who are prescribed protease inhibitors are associated with significantly increased CV mortality compared to the PLHIV who were prescribed a non-protease inhibitor ART regimen 8 . In another study, our group has also demonstrated that PLHIV with an ICD have a higher rate of ICD firing and subsequently an increased risk of CV mortality compared to the non-HIV individuals 14 . Therefore, from the previous results, it may be plausible that the poor HF outcomes among PLHIV are multifactorial, contributed by different elements.…”
Section: Discussionmentioning
confidence: 71%
“…These findings with respect to increased CV and all-cause mortality rates among PLHIV with HF (including preserved as well as reduced ejection fraction) expand upon previous findings by Freiberg et al based out of the US Veterans Aging Cohort Study-Virtual Cohort (VACS-VC) cohort (~97% male) suggesting that individuals with HIV and HF face increased mortality as compared with non-HIV-infected individuals with HF 4 especially those with a detectable VL/lower CD4 count. HIV is associated with increased CV mortality because of traditional CV risk factors, residual virally mediated inflammation despite of HIV treatment, side effects of ART 8,[14][15][16][17] . In the same cohort, we have previously shown that PLHIV who are prescribed protease inhibitors are associated with significantly increased CV mortality compared to the PLHIV who were prescribed a non-protease inhibitor ART regimen 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Alvi et al 4 demonstrated in 2018 that among HIV‐infected subjects with concomitant heart failure, the rate of appropriate ICD discharges was higher than in uninfected controls. Additionally, ICD discharge was associated with increased cardiovascular mortality among both HIV‐infected and uninfected controls with heart failure 4 . However, this study was limited to only subjects who had been admitted to the hospital for decompensated heart failure, which may represent a higher‐risk subgroup.…”
Section: Risk Of Ventricular Arrhythmias In Hiv‐infected Individuals mentioning
confidence: 99%
“…Ventricular arrhythmias that arise after cocaine use can be due to sodium channel blockade by the drug itself, a surge of sympathetic stimulation, and/or due to cocaine‐induced myocardial infarction 28 . Alvi et al 4 found that history of cocaine use was associated with greater likelihood of appropriate ICD discharge even after adjustment for history of coronary artery disease, CD4 count, use of beta blockers, QRS duration and higher NYHA class ( p = .011). Furthermore, cocaine use has been found to not only lead to decreased ART adherence but also to directly affect HIV disease progression independent of adherence to ARVs 29 .…”
Section: Substance Abusementioning
confidence: 99%
“…Furthermore, ICD data provides an objective surrogate for risk of sudden arrhythmic death, which would otherwise be presumed in studies without ICD data and/or autopsy data. Alvi et al 8 demonstrated that among HIV‐infected subjects with concomitant heart failure, rates of both appropriate and inappropriate ICD shock were higher than in uninfected controls. Additionally, ICD discharge was associated with increased cardiovascular mortality amongst both HIV‐infected and uninfected controls with heart failure 8 .…”
Section: Introductionmentioning
confidence: 99%